A Comparison of the Process and Content of Sexual Communications Among African American Adolescent Children Living in Parent and Grandparent Headed Families - Cornelius JB; Okoro F; Piper CN (Dove Medical Press, 2021)
Judith B Cornelius,1 Florence Okoro,1 Crystal N Piper2 1School of Nursing, University of North Carolina at Charlotte, Charlotte, NC, USA; 2Department of Public Health Sciences, University of North Carolina at Charlotte, Charlotte, NC, USACorrespondence: Judith B CorneliusSchool of Nursing, University of North Carolina at Charlotte, 9201 University City Blvd, CHHS 412B, Charlotte, NC 28223, USAEmail jbcornel@uncc.eduIntroduction: The process of parental sexual communication has been shown to delay the sexual debut of adolescents; however, few studies have focused on extended family members such as grandparents. The purpose of this study was to compare the process and content of sexual communications among African-American adolescent children living in parent or grandparent headed families.Methods: A secondary analysis of two de-identified datasets from 80 African-American adolescents was conducted.Results: Findings indicated that there were no significant differences in the sexual communication process in relation to facilitators p= 0.38 and barriers p =0.23 with the discussions. There were however significant differences with adolescents’ attitudes (p = 0.04) and feelings regarding sexual abstinence (p =0.01), HIV prevention (p= 0.002) and teen pregnancy (p= 0.010).Discussion: Researchers can use the results of this study as a beginning point in examining the sexual communication process in grandparent-headed families.Keywords: adolescents, parents, grand parents, sexual communications, process, content